IS IT POSSIBLE TO DIAGNOSE PARKINSONISM WITH THE HELP OF NEUROSTEROIDS? - Rakhimbaeva, G.S.; Okhunova, D.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
This article presents information and results of studies on the role of the hormones cortisol and dehydroepiandrosterone sulfate (DHEAS) in the diagnosis of cognitive impairment and dementia in Parkinson’s disease. The reasons for the relationship of cognitive impairment in Parkinson’s disease are described in detail in comparison with the results of neuropsychological tests. We examined 40 patients with PD, who were divided into 20 patients depending on the presence or absence of cognitive impairment and dementia. As a control, we also examined on a voluntary basis 20 healthy persons recognized as such by a special commission. The diagnostic efficacy of neurosteroids has been established, including the level of dehydroepiandrosterone sulfate and cortisol in the blood serum of patients for early diagnosis of cognitive impairment and monitoring the effectiveness of therapy, identifying a risk group in PD.